2006
DOI: 10.1002/ana.20871
|View full text |Cite
|
Sign up to set email alerts
|

Differential twin concordance for multiple sclerosis by latitude of birthplace

Abstract: Multiple sclerosis is similarly heritable by sex, and the apparent variation in MZ concordance by latitude is influenced by environmental and genetic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 43 publications
7
91
0
Order By: Relevance
“…We first demonstrated that twin concordance for multiple sclerosis was higher among MZ compared with DZ twins as expected, but the MZ:DZ concordance ratio was also increased by North European ancestry, younger age at diagnosis, and Northern latitude of birth (Islam et al, 2006), indicating gene-environment interaction. We then showed that sun exposure modified the risk of multiple sclerosis within disease-discordant MZ pairs (Islam et al, 2007).…”
Section: Multiple Sclerosissupporting
confidence: 59%
“…We first demonstrated that twin concordance for multiple sclerosis was higher among MZ compared with DZ twins as expected, but the MZ:DZ concordance ratio was also increased by North European ancestry, younger age at diagnosis, and Northern latitude of birth (Islam et al, 2006), indicating gene-environment interaction. We then showed that sun exposure modified the risk of multiple sclerosis within disease-discordant MZ pairs (Islam et al, 2007).…”
Section: Multiple Sclerosissupporting
confidence: 59%
“…The percentage of concordance for monozygotic twins is approximately 25-30% whereas the concordance percentage for dizygotic twins is 3-5% (Ebers et al, 1986(Ebers et al, , 1995(Ebers et al, , 2004Mumford et al, 1994;Willer et al, 2003;Hansen et al, 2005;Islam et al, 2006;Ristori et al, 2006). This concordance rate for fraternal twins is greater than that of other first-degree relatives of MS patients but is still far less than that of identical twins (Willer et al, 2003).…”
Section: Twin Studiesmentioning
confidence: 99%
“…Indeed, genetic epidemiological studies strongly support this. 10 It would have been of interest had the authors of the present study been able to incorporate a measure of vitamin D status along with their analysis of HLA-DRB1 alleles, however this is not an easy thing to do. More generally, epidemiological, functional, and genetic data are making a role for vitamin D in MS aetiology broadly unequivocal.…”
mentioning
confidence: 98%